2008
DOI: 10.1007/s10704-008-9262-y
|View full text |Cite
|
Sign up to set email alerts
|

Transient dynamic analysis of interface cracks in layered anisotropic solids under impact loading

Abstract: Transient elastodynamic crack analysis in two-dimensional (2D), layered, anisotropic and linear elastic solids is presented in this paper. A time-domain boundary element method (BEM) in conjunction with a multi-domain technique is developed for this purpose. Time-domain elastodynamic fundamental solutions for homogenous, anisotropic and linear elastic solids are applied in the present time-domain BEM. The spatial discretization of the boundary integral equations is performed by a Galerkin-method, while a collo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 29 publications
(25 reference statements)
3
16
0
Order By: Relevance
“…The dynamic stress intensity factors (opening and transverse shear modes) were computed as functions of the frequency of the incident wave. It was also shown that with decreasing frequency of the loading the dynamic solution tends to the static one, and the obtained numerical results are in a very good agreement with the static solutions [5][6][7].…”
supporting
confidence: 64%
See 2 more Smart Citations
“…The dynamic stress intensity factors (opening and transverse shear modes) were computed as functions of the frequency of the incident wave. It was also shown that with decreasing frequency of the loading the dynamic solution tends to the static one, and the obtained numerical results are in a very good agreement with the static solutions [5][6][7].…”
supporting
confidence: 64%
“…2 and 3, where 3-D distributions of normal and tangential displacements at the bonding interface are given for the dimensionless wave number k ð1Þ 2 a ¼ wa=c ð1Þ 2 ¼ 0:25 and the dimensionless distance between cracks d/a=5. The given displacements are normalized by the factor 2μ 0 /aσ 0 , where σ 0 is the stress amplitude of the incident wave and the factor μ 0 was specified as follows [7]: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the substantially more complex solution, if compared to the case of cracks in homogeneous materials, the possible contact interaction was neglected in the above papers. A similar simplification was also used by Bouden et al (1991), Zhang (1991), Qu (1994Qu ( , 1995, Wang and Gross (2001), Mykhas'kiv et al (2009), Wünsche et al (2009). To overcome the difficulties and to avoid the regularization and numerical evaluation of the hypersingular integrals, the modified system of boundary integral equations was proposed by Menshykova et al (2009).…”
mentioning
confidence: 99%
“…A time domain BEM in conjunction with a multi-domain technique was developed in [31] for transient dynamic interior or interface crack analysis in 2D, layered, anisotropic elastic solids. In the paper, the effects of the crack configuration, the material anisotropy, the layer combination and the dynamic loading on the dynamic stress intensity factors and the scattered elastic wave fields were investigated.…”
Section: Introductionmentioning
confidence: 99%